SEDIMENTARY SIGNATURES AND PROCESSES DURING MARINE BOLIDE IMPACTS: A REVIEW - Dypvik H.; Jansa L.F. (My University, 2003)
Studies of submarine impact craters resulting from impacts of comets or asteroids demonstrate that the presence of water and the physical properties of target rocks have a major influence on sedimentary processes associated with meteorite impacts. This results in difference in sedimentary signature of bolide impacts in marine environments compared to subaerial impact craters. In subaerial impacts, the targets are commonly hard rocks, frequently of igneous and/or metamorphic origin, whereas in submarine impacts, the targets are mostly unconsolidated or poorly lithified sediments, or sedimentary rocks, with high volumes of pore water. Such differences result in variability in crater morphology and in sedimentary processes inside and outside the impact area.
Keywords: Montagnais; Mjølnir; Submarine craters; Sedimentary processes; Mega-tsunami